Beliefs on the ability to regulate negative emotions mediates the effects of competitive anger on task-focused self-efficacy in taekwondo athletes - Luca Bovolon; Maria Rosaria Nappa; Salvatore Chiodo; Francesca Greco; Katia Folino; Maria Grazia Tarsitano; Maurizio Bertollo; Gian Pietro Emerenziani (Heliyon)
Self-efficacy (SE) refers to an individual's belief in their own ability to successfully execute specific tasks and produce desired outcomes. The focused SE on specific sports tasks has been shown to impact athletic performance by interacting with other self-evaluation processes, like self-efficacy beliefs in emotion-related regulation and effective emotion regulation. This study aims at investigating the mediating effect of SE in regulating negative affect in the relationship between anger and taekwondo task-focused SE. Accordingly, the study aims to adapt and validate the Roundhouse Kick Self-Efficacy Scale (RKSES) in Italian, which assesses taekwondo task-focused SE in athletes.In study 1, 180 Italian taekwondo athletes (Mage = 27.6, SD = 12; 89.4 % black belts; 69 women) were sampled to validate the Italian version of the RKSES, which presented a good fit of the data (p = .031), internal consistency (α = .916), and concurrent validity (r = .561). Study 2 involved 357 Italian taekwondo athletes (Mage = 28.4, SD = 11.87; 87.4 % black belts; 147 women), and collected self-reports on regulating negative emotions SE, competitive anger and aggression, perceived physical ability, and taekwondo task-focused SE. Analysis of covariance revealed multiple differences between age-related categories in terms of competitive anger (p < .001) and aggressiveness (p = .041), and between gender groups in terms of competitive aggressiveness (p = .002), negative emotion regulation SE (p = .024), and perceived physical abilities (p < .001). Mediation analysis indicated that negative emotion regulation SE partially mediated the effects of competitive anger on task-focused SE (p < .001).Findings suggest a mediating role of negative emotion regulation SE in the relationship between competitive anger and task-focused SE, emphasizing the importance of taking an instrumental approach to emotion regulation, and advocates for the use of practical tools to assess task-focused SE.